What actions promote a positive ethical climate? A critical incident study of nurses’ perceptions - Silén, Marit (Nursing ethics, 2012)
Few qualitative studies explore the phenomenon of positive ethical climate and what actions are perceived as promoting it. Therefore, the aim of this study was to explore and describe actions that acute care ward nurses perceive as promoting a positive ethical climate. The critical incident technique was used. Interviews were conducted with 20 nurses at wards where the ethical climate was considered positive, according to a previous study. Meeting the needs of patients and next of kin in a considerate way, as well as receiving and giving support and information within the work group, promoted a positive ethical climate. Likewise, working as a team with a standard for behaviour within the work group promoted a positive ethical climate. Future research should investigate other conditions that might also promote a positive ethical climate.